2006
DOI: 10.1590/s1516-89132006000100017
|View full text |Cite
|
Sign up to set email alerts
|

Helminths of the marine tucuxi, Sotalia fluviatilis (Gervais, 1853) (Cetacea: Delphinidae), in northern Rio de Janeiro State, Brazil

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…S. guianensis inhabits coastal waters, whereas S. longirostris prefers oceanic bays and island regions. A. typica larvae has been reported in Thunnus thynnus and Auxis thazard off Rio de Janeiro [28] , [29] , [30] , [31] , [32] , indicating that the parasite is common in the area. During summer, there is an increase in whale-watching along the Rio de Janeiro coast, which is probably related to the seasonal upwelling in the region responsible for the addition of new elements to the food webs.…”
Section: Discussionmentioning
confidence: 99%
“…S. guianensis inhabits coastal waters, whereas S. longirostris prefers oceanic bays and island regions. A. typica larvae has been reported in Thunnus thynnus and Auxis thazard off Rio de Janeiro [28] , [29] , [30] , [31] , [32] , indicating that the parasite is common in the area. During summer, there is an increase in whale-watching along the Rio de Janeiro coast, which is probably related to the seasonal upwelling in the region responsible for the addition of new elements to the food webs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a parasitological survey of over 300 cetacean individuals from 13 species stranded on the coast of England and Wales (Gibson et al , 1998) revealed that Campula oblonga occurred almost exclusively in harbour porpoises, Phocoena phocoena . Likewise, Synthesium pontoporiae is restricted to the franciscana dolphin, Pontoporia blainvillei , in the South American Atlantic (Andrade et al , 2001; Melo et al , 2006; Berón-Vera et al , 2008; Marigo et al , 2008, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The fauna of small coastal Cetacea of the sampling area offers a diverse range of possible definitive hosts for A. typica , which is reflected in its relatively high prevalence in both T. lepturus and N. tripes ( Dupuy & Maigret, 1976 ; Smeenk, Leopold & Addink, 1992 ; Hutterer, 1994 ; Robineau & Vely, 1997 ; Van Waerebeek et al, 1999 ; Felix & Van Waerebeek, 2005 ; Wenzel et al, 2009 ; Weir et al, 2011 ; Weir et al, 2014 ; Jung et al, 2016 ). A predator–prey relationship between dolphins from the genus Sotalia spp., which are a definitive host for A. typica , and T. lepturus was previously described ( Melo et al, 2006 ; Carvalho et al, 2008 ). As a typical shelf inhabitant with a broad spectrum of intermediate hosts and pelagic life-cycle, infestation with A. typica was expected in the studied fishes.…”
Section: Discussionmentioning
confidence: 99%